2008
DOI: 10.1016/j.molcel.2007.12.026
|View full text |Cite
|
Sign up to set email alerts
|

Structure of a BCOR Corepressor Peptide in Complex with the BCL6 BTB Domain Dimer

Abstract: The transcriptional corepressors BCOR, SMRT, and NCoR are known to bind competitively to the BCL6 BTB domain despite the fact that BCOR has no detectable sequence similarity to the other two corepressors. We have identified a 17 residue motif from BCOR that binds directly to the BCL6 BTB domain and determined the crystal structure of the complex to a resolution of 2.6 A. Remarkably, the BCOR BCL6 binding domain (BCOR(BBD)) peptide binds in the same BCL6 binding site as the SMRT(BBD) peptide despite the lack of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
224
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 153 publications
(228 citation statements)
references
References 24 publications
4
224
0
Order By: Relevance
“…Transcription factors with a BTB domain at the N-terminus comprise a large important class of molecules involved in development and carcinogenesis. As shown in crystallographic studies, the BTB domains from PLZF (promyelocytic leukemia zinc finger), 2,3 BCL6, 4,5 LRF/ZBTB7, 6,7 Bach1, 8 and FAZF 9 are tightly interwound homodimers. In the case of Miz1, there are contradicting crystallographic data that BTB exists as either homodimer 9 or homotetramer.…”
Section: Introductionmentioning
confidence: 89%
“…Transcription factors with a BTB domain at the N-terminus comprise a large important class of molecules involved in development and carcinogenesis. As shown in crystallographic studies, the BTB domains from PLZF (promyelocytic leukemia zinc finger), 2,3 BCL6, 4,5 LRF/ZBTB7, 6,7 Bach1, 8 and FAZF 9 are tightly interwound homodimers. In the case of Miz1, there are contradicting crystallographic data that BTB exists as either homodimer 9 or homotetramer.…”
Section: Introductionmentioning
confidence: 89%
“…4,18,19 Recently, the OFCD with BCOR mutation Y Kondo et al minimal BCL-6 binding site was identified within residues 498-514, which is located in exon 4. 20 In this study, a novel BCOR mutation, c.888delG (p.N297IfsX80) in exon 4, was found in this family. We assumed the mutant transcript with this mutation may undergo nonsense-mediated mRNA decay, but we could not confirm it as no living cells were available from the patients.…”
Section: Resultsmentioning
confidence: 51%
“…Both NCOR and SMRT bind to BCL6 via a conserved 17-residue BCL6 binding domain (BBD) [37]. BCOR forms a completely different type of complex than NCOR and SMRT [39]. Specifically, BCOR associates with a polycomb/ubiquitin ligase complex containing RING1, RYBP, NSPC1, RNF2, FBXL10 and Skp1 (S-phase kinase-assocated protein 1) [40].…”
Section: Biochemical Mechanisms Of Action Of Bcl6mentioning
confidence: 99%
“…Specifically, BCOR associates with a polycomb/ubiquitin ligase complex containing RING1, RYBP, NSPC1, RNF2, FBXL10 and Skp1 (S-phase kinase-assocated protein 1) [40]. The BBDs of NCOR and SMRT are identical, whereas the BCOR BBD is completely different, yet all three bind to the BCL6 BTB lateral groove in perfectly overlapping configurations [37,39]. BCL6 appears to recruit two distinct repression complexes at promoters and enhancers via its BTB domain [41].…”
Section: Biochemical Mechanisms Of Action Of Bcl6mentioning
confidence: 99%